Toán Lớp 9: Cho P= ($\frac{x+3\sqrt{x}+2 }{(x\sqrt{x}+2)(\sqrt{x}-1) }$ – $\frac{x+\sqrt{x} }{x-1}$) :($\frac{1}{\sqrt{x}+1}$ – $\frac{1}{\sqrt{x

Question

Toán Lớp 9: Cho P= ($\frac{x+3\sqrt{x}+2 }{(x\sqrt{x}+2)(\sqrt{x}-1) }$ – $\frac{x+\sqrt{x} }{x-1}$) :($\frac{1}{\sqrt{x}+1}$ – $\frac{1}{\sqrt{x}-1 }$ )
a) Rút gọn P
b) Tìm x để $\frac{1}{p}$ -$\frac{\sqrt{x}+1 }{8}$ $\geq$ 1, hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Nhã Trúc 6 ngày 2022-06-18T00:12:34+00:00 1 Answer 0 views 0

TRẢ LỜI ( 1 )

  1. Giải đáp:
    $\begin{array}{l}
    a)Dkxd:x \ge 0;x \ne 1\\
    P = \left( {\dfrac{{x + 3\sqrt x  + 2}}{{\left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}} – \dfrac{{x + \sqrt x }}{{x – 1}}} \right)\\
    :\left( {\dfrac{1}{{\sqrt x  + 1}} – \dfrac{1}{{\sqrt x  – 1}}} \right)\\
     = \left( {\dfrac{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  + 2} \right)}}{{\left( {\sqrt x  + 2} \right)\left( {\sqrt x  – 1} \right)}} – \dfrac{{\sqrt x \left( {\sqrt x  + 1} \right)}}{{\left( {\sqrt x  – 1} \right)\left( {\sqrt x  + 1} \right)}}} \right)\\
    :\dfrac{{\sqrt x  – 1 – \sqrt x  – 1}}{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}\\
     = \left( {\dfrac{{\sqrt x  + 1}}{{\sqrt x  – 1}} – \dfrac{{\sqrt x }}{{\sqrt x  – 1}}} \right).\dfrac{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}{{ – 2}}\\
     = \dfrac{1}{{\sqrt x  – 1}}.\dfrac{{\left( {\sqrt x  + 1} \right)\left( {\sqrt x  – 1} \right)}}{{ – 2}}\\
     = \dfrac{{\sqrt x  + 1}}{{ – 2}}\\
     =  – \dfrac{{\sqrt x  + 1}}{2}\\
    b)\dfrac{1}{P} – \dfrac{{\sqrt x  + 1}}{8} \ge 1\\
     \Leftrightarrow 1:\left( { – \dfrac{{\sqrt x  + 1}}{2}} \right) – \dfrac{{\sqrt x  + 1}}{8} – 1 \ge 0\\
     \Leftrightarrow \dfrac{{ – 2}}{{\sqrt x  + 1}} – \dfrac{{\sqrt x  + 1}}{8} – 1 \ge 0\\
     \Leftrightarrow \dfrac{{ – 16 – {{\left( {\sqrt x  + 1} \right)}^2} – 8\left( {\sqrt x  + 1} \right)}}{{8\left( {\sqrt x  + 1} \right)}} \ge 0\\
     \Leftrightarrow  – 16 – x – 2\sqrt x  – 1 – 8\sqrt x  – 8 \ge 0\\
     \Leftrightarrow  – x – 26\sqrt x  – 9 \ge 0\\
     \Leftrightarrow x + 26\sqrt x  + 9 \le 0\left( {ktm} \right)\\
    Vậy\,x \in \emptyset 
    \end{array}$

Leave an answer

Browse

12:2+4x4-12:2-5x3 = ? ( )